Comparative transcriptional profiling of tildipirosin-resistant and sensitive Haemophilus parasuis - Zhixin Lei (Nature Portfolio, 2017)
Abstract Numerous studies have been conducted to examine the molecular mechanism of Haemophilus parasuis resistance to antibiotic, but rarely to tildipirosin. In the current study, transcriptional profiling was applied to analyse the variation in gene expression of JS0135 and tildipirosin-resistant JS32. The growth curves showed that JS32 had a higher growth rate but fewer bacteria than JS0135. The cell membranes of JS32 and a resistant clinical isolate (HB32) were observed to be smoother than those of JS0135. From the comparative gene expression profile 349 up- and 113 downregulated genes were observed, covering 37 GO and 63 KEGG pathways which are involved in biological processes (11), cellular components (17), molecular function (9), cellular processes (1), environmental information processing (4), genetic information processing (9) and metabolism (49) affected in JS32. In addition, the relative overexpression of genes of the metabolism pathway (HAPS_RS09315, HAPS_RS09320), ribosomes (HAPS_RS07815) and ABC transporters (HAPS_RS10945) was detected, particularly the metabolism pathway, and verified with RT-qPCR. Collectively, the gene expression profile in connection with tildipirosin resistance factors revealed unique and highly resistant determinants of H. parasuis to macrolides that warrant further attention due to the significant threat of bacterial resistance.